2020
DOI: 10.1021/acs.energyfuels.0c00845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 and H2O on Char Properties. Part 2: In Situ and Ex Situ Char in Oxy-Steam Combustion

Abstract: The physical and chemical properties of H2O (oxy-steam combustion) and N2 (air combustion) are different, which has influence on the char properties in oxy-steam combustion. Measuring in situ char (without any cooling) kinetic parameters is very important, especially at oxy-steam atmosphere. Both in situ and ex situ char properties were investigated in this paper. Ex situ char was obtained at different cooling rates. Char properties were measured by X-ray diffraction, H/C ratio, Raman spectrum, and specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In our previous studies, it was reported that steam indeed influenced the char properties and combustion/gasification reaction rates in oxy-steam combustion. ,, For instance, coal char is much developed and disordered after pyrolysis at a steam-containing atmosphere . As a result, the char combustion rate is higher at the oxy-steam atmosphere than that at the O 2 /CO 2 atmosphere . Furthermore, regarding the char combustion rate in O 2 /CO 2 /H 2 O, char-O 2 , char-CO 2 , and char-H 2 O reactions were found to compete for the carbon active sites. ,, Even in a high oxygen atmosphere, which means oxygen is excessive for char combustion, char-H 2 O still locally reacts with carbon active sites inside the char particles.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In our previous studies, it was reported that steam indeed influenced the char properties and combustion/gasification reaction rates in oxy-steam combustion. ,, For instance, coal char is much developed and disordered after pyrolysis at a steam-containing atmosphere . As a result, the char combustion rate is higher at the oxy-steam atmosphere than that at the O 2 /CO 2 atmosphere . Furthermore, regarding the char combustion rate in O 2 /CO 2 /H 2 O, char-O 2 , char-CO 2 , and char-H 2 O reactions were found to compete for the carbon active sites. ,, Even in a high oxygen atmosphere, which means oxygen is excessive for char combustion, char-H 2 O still locally reacts with carbon active sites inside the char particles.…”
Section: Introductionmentioning
confidence: 94%
“…15 As a result, the char combustion rate is higher at the oxy-steam atmosphere than that at the O 2 /CO 2 atmosphere. 14 Furthermore, regarding the char combustion rate in O 2 /CO 2 /H 2 O, char-O 2 , char-CO 2 , and char-H 2 O reactions were found to compete for the carbon active sites. 8,13,16 Even in a high oxygen atmosphere, which means oxygen is excessive for char combustion, char-H 2 O still locally reacts with carbon active sites inside the char particles.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations